Juridical Analysis of the Application of Reverse Proof in Corruption Cases - Rahayu, Edi Bagus Waluyo Yuda Teguh; Sidarta, Dudik Djaja; Subekti, Subekti (Ipso Jure, 2026)
This article discusses the juridical construction and implications of applying reverse burden of proof in corruption cases in Indonesia, with emphasis on its relation to the principle of legality and the presumption of innocence as fundamental principles in criminal law. The application of reverse burden of proof as regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 has sparked juridical debate regarding the extent to which this mechanism can be accepted within the framework of a rule-of-law state that upholds the principles of a fair trial and the protection of citizens' constitutional rights. Through a normative juridical research method, this article examines the normative tensions that arise when reverse burden of proof is confronted with the principle of non-self-incrimination and the concept of unlawful acts as essential elements in corruption crimes. The analysis results indicate that reverse burden of proof has a legitimate basis as an effort to combat corruption, which is considered an extraordinary crime, but its use must be positioned as a right, not an obligation of the defendant. Furthermore, its application cannot replace the state's duty to legally prove the elements of a criminal act, particularly the element of unlawfulness. Thus, the reverse burden of proof mechanism must be understood as a limited and balanced evidentiary strategy, to ensure that the judicial process remains within constitutional boundaries.